COMPARISON OF THE JUDICIAL FORGIVENESS (RECHTERLIJK PARDON) BETWEEN CIVIL LAW SYSTEM AND ISLAMIC LAW SYSTEM (FINDING THE FORMULATION OF THE PRINCIPLE OF RECHTERLIJK PARDON IN INDONESIAN CRIMINAL LAW) - Budimansyah; Prija Djatmika; Rachmad Safa’at; Setiawan Noerdajasakti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study falls under the category of normative legal research or doctrinal legal research. Primary legal resources, secondary legal materials, and tertiary legal materials are all used library research techniques for gathering legal materials (library research). In contrast, the descriptive analysis approach is used for data processing. According to the conclusions of this study, various civil law system nations, like the Netherlands, Greece, and Portugal, use the principle of judicial forgiveness (rechterlijk pardon). However, long before these nations implemented the principle of forgiveness (rechterlijk pardon) in their criminal law, Islamic criminal law used principle of forgiveness first in jarimah qadzaf (accusing adultery), jarimah qishas-diyat, and jarimah Ta'zir. Compared to the principle of forgiveness (rechterlijk pardon) in the civil law system, the principle of forgiveness (rechterlijk pardon) in Islamic criminal law offers benefits. The formulation of the principle of judicial forgiveness (rechterlijk pardon) in Indonesian criminal law in the future is to prescribe the principle of judicial forgiveness in Islamic criminal law since it is seen to have advantages. Furthermore, incorporating the notion of judicial forgiveness (rechterlijk pardon) from Islamic criminal law into Indonesian criminal law is sociologically consistent with the legal knowledge of the Indonesian people, the majority of whom are Muslims.